Rural tourism-an opportunity to achieve sustainable development goals: A study in Indian context - Amita Halder; Sanjay Kumar (National Geographical Journal of India, 2023)
According to UNWTO 2012 (United Nation World Tourism Organization), “Tourism has a great potential to accelerate progress across the Sustainable Development Goals” (SDGs). In India, rural tourism is one of the modern and emerging concepts, gaining popularity for playing a significant role in rural development. This is an alternative livelihood through which local people are getting social, economic, and cultural benefits. And, the Ministry of Tourism is also focusing on creating rural tourism projects. At present, Govt. of India has 107 rural tourism projects in 29 States which is an initiative towards AtmaNirbhar Bharat and Sustainable Development in rural areas of India. Many goals of Sustainable Development are directly and indirectly related to the objectives of rural tourism and the Govt. of India wants to rejuvenate this to gain self-economic growth after the COVID-19 outbreak. So, this paper focused on how sustainable development goals like gender equality; decent work, economic growth, etc. are connected with rural tourism. This paper is based on content analysis techniques and secondary data like reports from the Ministry of Tourism, reports on evaluation cum impact study of rural tourism projects (2011), India Tourism Statistics (2022), National Sample Survey Office report, and National Tourism Policies, Internet and Mobile Association of India report on homestay. The paper provides an overview of the connection of rural tourism and SDGs and how it is helping to achieve some sustainable development goals in India.